Competencias del trabajador social frente a la discriminación y bullying hacia los migrantes venezolanos en el cantón El Guabo - Samaniego Coello, Andrea Gabriela (My University, 2021)
The purpose of this work is to expose the migratory situation of Venezuelan citizens and its negative impact around their compulsory displacement, where elements such as discrimination, xenophobia and marginalization towards young people, boys and girls have an impact. On the other hand, the violation of rights is presented in a subtle or almost imperceptible way, from a low salary, offensive nicknames, denial of some basic or health service. Discrimination is latent in adults, youth and children, depriving them of true social equality and social autonomy, among others. The objective of the research is to explain the repercussion of social discrimination and the alternative solutions taken by the control bodies in the face of such problems within the El Guabo canton. The problem starts from a theoretical interpretation, based on bibliographic reviews with scientific contributions that aims to expose the competencies of Social Work and its ability to integrate values and skills in a professional way with the premise of promoting human and community well-being and the reintegration of their rights of Venezuelan migrants settled within the El Guabo canton.
El presente trabajo tiene como propósito exponer la situación migratoria de los ciudadanos venezolanos y su afectación negativa en torno a su desplazamiento obligatorio, donde inciden elementos como la discriminación, xenofobia y marginación hacia los jóvenes, niños y niñas. Por otra parte, la transgresión de derechos se presenta de forma sutil o casi imperceptible, desde un sueldo bajo, sobrenombres ofensivos, negación de algún servicio básico o de salud. La discriminación es latente en adultos, jóvenes y niños, privándolos de una verdadera igualdad social y autonomía social, entre otros. El objetivo de la investigación es explicar la repercusión de la discriminación social y las alternativas resolutorias que toman los organismos de control ante tales problemáticas dentro del cantón El Guabo. La problemática parte una interpretación teórica, con base fundamental en revisiones bibliográficas con aportes científicos que pretende exponer las competencias del Trabajo Social y su capacidad de integrar los valores y habilidades de forma profesional con la premisa de promover el bienestar humano, comunitario y la reintegración de sus derechos de los migrantes venezolanos asentados dentro del cantón El Guabo.
Keywords: MIGRACION; BULLYING; DISCRIMINACION; TRABAJO SOCIAL